Climate Change and Fiscal Policy : A Report for APEC - World Bank (World Bank, 2012)
Asia-Pacific Economic Cooperation (APEC) economies display large variation in terms of income per capita. The richest APEC economies have an income per capita about twenty times higher than the poorest ones. So far most work on fiscal policy and climate change has been written with developed economies in mind. This report on the use of fiscal policies for mitigating and adapting to climate change effects corrects that bias with a particular focus on the developing economies of APEC. It also plays close attention to lessons that could be learnt from the advanced economies of APEC and elsewhere. On mitigation, the report notes that achieving the ambitious targets adopted by APEC economies will depend crucially the choice of fiscal policy instruments. These choices will depend, in turn, on the characteristics of developing economies, particularly of their energy sectors. Specifically, mitigation in developing countries requires a broad-based response with four key components. First, carbon pricing will be critical, but will not be sufficient and in some economies and some sectors may have little or no impact due to pre-existing distortions. Second, energy sector reforms that liberalize markets and establish effective regulators so that policies can support appropriate carbon prices and cost pass-through in the energy sector will be key. Third, broader economic reforms may also be important to off-set current bias towards capital and energy intensive economic growth. Fourth, technology-based mitigation policies will also be needed, but, given the mixed track record in this area, must be chosen with care. Given the many uncertainties involved, and the multiple reforms needed, a verifiable quantity anchor for mitigation policy is recommended for developing economies, such as the energy-intensity target recently adopted by China. On the adaptation side, fiscal analysis has so far largely focused on cost projections, but for policy makers adaptation instruments and decision-making tools are as or more important. Adaptation instruments include the provision of public and club goods (such as infrastructure), public sector pricing reform (in particular of water) and financial instruments (microcredit and insurance) which can be cost-effective alternatives to subsidies. Key to the right choice of instruments (which will vary from location to location) will be the correct use of appropriate decision-making tools. In particular, the social costs and benefits of alternative strategies need to be analyzed under conditions of uncertainty, in many ways the hallmark of climate change. Popular tools such as multi-criteria analysis, vulnerability indexes, and cost- effectiveness analysis are inadequate to the task. A combination of Monte Carlo and 'real options' analysis within a cost-benefit framework is recommended for adaptation projects. Examples from a range of economies are provided to demonstrate the utility of such an approach.